Passive drag reduction of square back road vehicles - Altaf, Alaman; Omar, Ashraf Ali; Asrar, Waqar (Elsevier Ltd., 2014)
Bluff body vehicles such as trucks and buses do not have a streamlined shapes and hence have high drag which can be reduced to make great savings in operational cost. While rectangular flaps have been widely studied as both passive add-ons and in active drag reducing systems for bluff bodies, changing the basic geometry of the flap has not been explored in literature. In this work, a baseline drag value is obtained for a simplified MAN TGX series truck in a CFD software, and the drag reduction of a proposed elliptically shaped flap is compared to aerodynamically equivalent rectangular flaps. The optimal mounting angle for both flaps is found to be 501. A parametric study of changing the ellipse semi-major axis is carried out to find the optimal length for drag reduction. A maximum drag reduction of 11.1% is achieved using an elliptical flap with 0.12 m semi-major axis; compared to 6.37% for a length equivalent rectangular flap, and 6.84% for a surface area equivalent rectangular flap. Results of the pressure distribution and velocity flow behind the rear of the truck are also given and analyzed.